Developing ecological indicators of sustainable tourism in new protected areas: a case study of saline steppe and forest steppe habitats in Serbia - Stojanović, Vladimir; Delić, Jadranka; Perić, Ranko; Dunjić, Jelena; Obradović, Sanja (Turizam, 2021)
This paper is one of the results of three years research (2016-2019) of specific habitats of saline steppes and forest steppes along the Mostonga River, in the northern part of Serbia (Autonomous Province of Vojvodina), with the aim of their valorization and protection in the future. Here is also situated a natural area in the process of protection known as "Middle Mostonga". An integral part of protection declaration procedure is the creation of so-called "Protection study", as a basic document for the planning of protection guidelines for certain natural areas. It also includes tourism development analysis that aims to analyze and suggest its future development. Therefore, the working group, composed of representatives of the Institute for Nature Conservation of Vojvodina Province in Novi Sad and the University of Novi Sad (Faculty of Sciences – Department of Geography, Tourism and Hotel Management), examined the opportunities for ecotourism development in the area of ​​"Middle Mostonga". The working group will be strongly dedicated to the interpretation of natural phenomena and processes, that are in many ways unique, but for employees in tourism sector and the tourism industry in general, still invisible and unrecognizable places. The goal is to forthwith frame the possibility for consistent application of sustainable development goals in the future protected area "Middle Mostonga" and its surroundings by setting a scheme of indicators of sustainable tourism.